Performance based design of Hospital Building in Surabaya under variety design alternative using SNI 1726-2019 – Case study: Redesign Building - Muhammad Sigit Darmawan; Raden Buyung Anugraha Affandi; Ridho Bayuaji; Yuyun Tajunnisa; Indra Komara; Sita Auliyah Rahmasari (Institut Teknologi Sepuluh Nopember, 2023)
Nowadays, At the present time, the occurrence of regular earthquakes all over the world is turning into a significant problem. The structures that make up hospitals are among the most significant buildings in a living society because, in the event that a potentially dangerous scenario emerges, they help to serve as a caring and healing unit for the human population. A hospital building is made up of three different components: the structural component, the non-structural component, and the functional component. Each of these components can have an effect, either directly or indirectly, on the management and operation of the hospital building. Each time a natural or non-natural cause causes devastation and disaster, the globe suffers. In such cases, hospital buildings are vital in term of treating victims and injured persons, and housing those who lost their homes. Therefore, hospital facilities should be planned and constructed with enough stiffness and strength to resist disasters and serve as shelters or housing units afterward. This study analyses a hospital in area of Surabaya which built using Indonesian standard provision SNI 1726-2012. Weak structural members of the hospital are identified. The analysis determined to study the behaviour of hospital building when subjected to seismic forces using ETABS using current provision SNI 1726-2019. The investigation determined that the effect of the lateral forces under P-delta effect on the hospital building. Two different conditions have been compared, e.g., existing model and alternative configuration using dual system method to determining the recommendation for current building to resist seismic forces under new regulation. As a result, existing structure of hospital building still meet the requirements, but to fill the condition in accordance with SNI 1726-2019, some modifications need to be improved.